MULTIMEDIA KATALOG BERBASIS ANDROID DENGAN MENGGUNAKAN APLIKASI ADOBE FLASH PADA IDEKU DEKAL JERSEY SALATIGA - Ahmad Zainudin; Rujiono (STEKOM PRESS, 2020)
Ideku dekal jersey salatiga is a creative economy business place in the field of sticker printing for vehicles and sportswear, where every product manufacture requires creative ideas from a designer in making patterns and motifs to make products that consumers want. However, most consumers choose images from Google and other printing companies, which affects designers who have to redesign a product design and pattern that makes production take longer. Based on these problems, this study aims to create and design an interactive Multimedia Catalog in Ideku Dekal Jersey Salatiga using Adobe Flash software based on Android which can be made into 2 types that can be opened on computers and on Android-based cellphones which will make it easier. consumers who order online and can still view the catalog even though they are far away without having to come to Ideku Dekal Jersey Salatiga directly.